Courtesy Visit by UMPSAs NC to meet the Honourable Chief Minister of Sabah - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KOTA KINABALU, 27 September 2023 - A delegation from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by Vice-Chancellor Professor Dato’ Ts. Dr. Yuserrie Zainuddin, who is also the Deputy Chairman of the UMPSA Foundation, met with the Honourable Chief Minister of Sabah, Datuk Seri Panglima Haji Hajiji Haji Noor, at the Chief Minister's Office in Kota Kinabalu recently.